(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
English has emerged as a global lingua franca, serving as a common language for communication among speakers of diverse native languages. This article explores the power of English in uniting the world by examining its historical development, widespread use in various domains, and impact on culture, education, and business. The adoption of English as a global language has facilitated cross-cultural communication, promoted economic development, and enhanced access to information and opportunities. However, the dominance of English has also raised concerns about linguistic diversity and cultural homogenization. Despite these challenges, the global reach of English continues to grow, highlighting its significance as a unifying force in the modern world.